International criminal court: a review - Prakash, K.P. (2002)
The International Criminal Court is at the centre of efforts to create a systme of justice that can establish accountability for gross violations of human rights. At the heart of the debate is how to lay a proper legal foundation for a process that will make such violations less common in this century than they were in the last one. - Reproduced.
Keywords: Judiciary